Is There a Relation Between Insertion/Deletion Polymorphism of the Angiotensin Converting Enzyme Gene in Patients of Migraine with Aura and Migraine without Aura in Region of Eastern Turkey? - Ozbey, Ulku; Etem, Ebru; Ozel, Seda; Berilgen, M. Said (Ortadogu Ad Pres & Publ Co, 2010)
Objective: Angiotensin-converting enzyme (ACE) is one of the key enzymes in the renin-angiotensin-aldosterone system which modulates vascular tension and blood pressure. Many authors have reported an association between ACE-D allele and coronary heart disease and other cardiovascular diseases. The mechanism underlying the positive associations between the ACE-D alleles and diseases are not yet clear. Alterations of the renin-angiotensin system have been implicated in the pathogenesis of various diseases. Several angiotensin I converting enzyme inhibitors and an angiotensin II receptor blocker were demonstrated to have a clinically important prophylactic effect in migraine. Previous reports showed an association between migraine without aura and ACE-D allele polymorphism. In this study it is aimed to evaluate whether the DD genotype could also be associated with the frequency and duration of migraine without aura (MoA) and migraine with aura (MwA). Material and Methods: One hundred one migraine patients (37 MoA, 64 MwA) and 101 healthy non-migrainous controls from the region of Eastern Turkey were included in this study. The genotype characteristics were determined by the PCR analysis using DNA extracted from peripheral blood. Results: There was no significant difference in allelic frequency (I and D) and genotype polymorphism (DD, DI and II) of the ACE gene in migraine patients and controls (genotype frequency: p=0.08). ACE genotype distribution was similar in migraine patients and healthy control groups. Turkish patients MoA and MwA did not show any difference in incidence of the ACE-DD genotype. Conclusion: We conclude that the I/D polymorphism at the ACE locus does not play any role in the pathogenesis and progression of migraine.
Türkiye'nin do?u bölgesinde auralı ve aurasız migren hastalarında anjiyotensin konverting enzim geninin i?nsersiyon/delesyon polimorfızmiyle i?lişkisi var mıdır?
Keywords: Migraine with aura; migraine without aura; headache; polymorphism, genetic